A new series of trivalent lanthanide (Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy) coordination polymers with a 1, 2-cyclohexanedicarboxylate ligand: synthesis, crystal structure, luminescence and catalytic properties. Issue 20 (3rd May 2016) - Russell, Samantha E.; Gosset, Cyrille; Agache, Xavier; Volkringer, Christophe; Henry, Natacha; Decadt, Roel; Van Deun, Rik; Visseaux, Marc; Loiseau, Thierry
Abstract : The lanthanide coordination complexes containing aliphatic cyclic dicarboxylate linker have been characterized for their luminescence and catalytic properties. Abstract : Eight lanthanide coordination polymers (Ln(1, 2-chdc)(form)(H2 O)) have been solvothermally synthesized from the reaction of 1, 2-cyclohexane dicarboxylic acid (denoted as 1, 2-chdcH2 ) with trivalent metallic cations (Ce 3+ (1 ), Pr 3+ (2 ), Nd 3+ (3 ), Sm 3+ (4 ), Eu 3+ (5 ), Gd 3+ (6 ), Tb 3+ (7 ) and Dy 3+ (8 ); from a nitrate or chloride source) in a mixed H2 O/ N, N -dimethylformamide solvent (DMF) at T = 100–150 °C (form = formate ligand). Their crystal structures are similar and built up from nine-fold coordinated lanthanide cations (LnO9 – tricapped trigonal prism), linked to each other through three Ln–O–Ln bonds (face sharing connection mode of LnO9 polyhedra) in order to generate infinite ribbons. The coordination sphere of the lanthanide center is ensured by oxygen atoms from the 1, 2-chdcH2 ligand and formate groups. The latter come from the partial solvothermal decomposition of DMF solvent. The resulting compounds exhibit a layered structure with infinite chains of LnO9, connected to each other via the ditopic 1, 2-chdc linker. Luminescence studies (steady-state excitation, emission and time-resolved decay measurements) have been performed on the compounds bearing Ce 3+, Nd 3+, Sm 3+, Eu 3+, Tb 3+, and Dy 3+ cations. The Nd compound (3 ) was found to be efficient for isoprene (methyl-2-butadiene, CH2 CH–C(Me)CH2 ) polymerization despite the presence of water in its molecular structure, affording a highly cis stereo-regular polymer.